Care and social integration in European societies - Geissler, Birgit; Pfau-Effinger, Birgit (Book collections on Project MUSE., 2005)
This book provides invaluable descriptions and comparative analyses of the now complex and highly varied arrangements for the care of children, disabled and older people in Europe, set within the context of changing labour markets and welfare systems. Issues of gender, family change, social integration and citizenship are all explored in a series of chapters that report on original empirical, cross-national research.